Systematics of Drosera sect. Drosera s.s. (Droseraceae) - Gonella, Paulo Minatel (2017)
Drosera is a carnivorous plant genus belonging to the Droseraceae and comprising around 250 species distributed worldwide. A great number of new species and combinations have been published for Brazil and the Neotropics in the past decades; however, a comprehensive taxonomic work dealing with these species was still lacking. Furthermore, previous phylogenetic works on the genus focused on understanding the relationships between the morphological and geographical groups, revealing that all proposed infrageneric classifications were incongruent with the phylogeny and that the Neotropical species belonging to D. sect. Drosera are divided into two lineages mostly defined by chromosome number. In the present work, a comprehensive taxonomic treatment for the Brazilian Drosera is presented, together with a revision of the previously poorly known Andean species, descriptions of new species and a molecular phylogeny focusing on the two Neotropical lineages of D. sect. Drosera. Although the phylogenetic analyses here performed did not present conclusive results regarding relationships at the species level, they shed light on the importance of some morphological traits for the classification of these species and back up the species circumscriptions adopted in recent works. Combined with data covering all the other lineages in a global phylogeny of Drosera, these results will be of crucial importance for the proposition of a new infrageneric classification of the genus